1977
DOI: 10.1063/1.434988
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam electric resonance study of formaldehyde, thioformaldehyde, and ketene

Abstract: Articles you may be interested inA semiempirical theoretical study of the [2+2] cycloaddition between ketene and formaldehyde AIP Conf. Proc. 330, 222 (1995); 10.1063/1.47652 Molecular beam electric resonance study of the ground and excited states of cyanoacetylene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(83 citation statements)
references
References 36 publications
11
72
0
Order By: Relevance
“…These parameters reproduce the ab initio dipole moment values of the µA 1 , µB 1 , and µB 2 components with rms errors of 0.0002 Debyes for each component. The equilibrium value of our dipole moment is 2.3778 D (at r e CO = 1.2033742Å, r e CH = 1.10377Å, θ e OCH = 121.844 • ), which can be compared to the experimental value of the ground vibrational state dipole moment of µ=2.3321(5) D measured by Fabricant et al (1977). The eigenvectors, obtained by diagonalization, are used in conjunction with the DMS to compute the required linestrengths (and from that the Einstein-A coefficients and absolute intensities) of transitions that satisfy the rotational selection rules…”
Section: Dipole Moment Surface and Intensitiesmentioning
confidence: 99%
“…These parameters reproduce the ab initio dipole moment values of the µA 1 , µB 1 , and µB 2 components with rms errors of 0.0002 Debyes for each component. The equilibrium value of our dipole moment is 2.3778 D (at r e CO = 1.2033742Å, r e CH = 1.10377Å, θ e OCH = 121.844 • ), which can be compared to the experimental value of the ground vibrational state dipole moment of µ=2.3321(5) D measured by Fabricant et al (1977). The eigenvectors, obtained by diagonalization, are used in conjunction with the DMS to compute the required linestrengths (and from that the Einstein-A coefficients and absolute intensities) of transitions that satisfy the rotational selection rules…”
Section: Dipole Moment Surface and Intensitiesmentioning
confidence: 99%
“…The molecular parameters determined from their work, which include one sextic-order centrifugal distortion parameter, allowed frequency predictions through the 300 GHz region with less than 500 kHz error. Five years later, Fabricant et al (1977) measured an improved dipole moment of 1.6491(4) D.…”
Section: à9mentioning
confidence: 99%
“…The rotational constants used to derive the line frequencies were taken from the CDMS Catalog 2 for H 2 CS (Maeda et al 2008) and H 2 13 CS. The H 2 CS dipole moment, μ = 1.6491D, is the one measured by Fabricant et al (1977). For H 2 C 34 S (ortho and para) and HDCS, the line parameters were fitted from all rotational lines reported by Minowa et al (1997) and the observed lines towards B1 dark cloud by Marcelino et al (2005).…”
Section: H 2 Csmentioning
confidence: 99%